Back Cover: Teaching new tricks to old dogs: A review of drug repositioning of disulfiram for cancer nanomedicine (View 4/2021). Issue 5 (27th October 2021) - Zhao, Pengfei; Tang, Xueping; Huang, Yongzhuo
Abstract : The back cover page of article number 20200076, Gungun Lin displays that the intrinsic magneto‐physical properties of magnetic particles can be explored to enable multidimensional cellular phenotyping and biomolecular analysis.